2018
DOI: 10.1016/j.eurpsy.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term reduction of seclusion and forced medication on a hospital-wide level: Implementation of an open-door policy over 6 years

Abstract: This underlines the potential of the introduction of an open-door policy to attain a long-term reduction in involuntary measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 24 publications
0
18
0
2
Order By: Relevance
“…Due to the rising number of cases treated in the UPK, the percentage of involuntary admission decreased from 13.8% in 2000 (33) to 10.6% in 2013–2015. This might have exerted a positive effect on the mean clinical severity of cases and on the therapeutic atmosphere, further supporting the positive effects of the introduction of an open-door strategy in the hospital (22, 28, 29). In total, the frequency of involuntary admissions in our study is within the range found across Europe, with a minimum of 12.4 per 100,000 inhabitants in Italy and up to 232.5 per 100,000 inhabitants in Finland and with considerable national and regional variations (20, 39).…”
Section: Discussionmentioning
confidence: 70%
“…Due to the rising number of cases treated in the UPK, the percentage of involuntary admission decreased from 13.8% in 2000 (33) to 10.6% in 2013–2015. This might have exerted a positive effect on the mean clinical severity of cases and on the therapeutic atmosphere, further supporting the positive effects of the introduction of an open-door strategy in the hospital (22, 28, 29). In total, the frequency of involuntary admissions in our study is within the range found across Europe, with a minimum of 12.4 per 100,000 inhabitants in Italy and up to 232.5 per 100,000 inhabitants in Finland and with considerable national and regional variations (20, 39).…”
Section: Discussionmentioning
confidence: 70%
“…This does not necessarily have to result in an increase of seclusion or coercive interventions in general. On the contrary, there is evidence that coercive interventions including seclusion can be significantly reduced by the introduction of an open-door policy [ 11 , 14 , 37 ]. Furthermore, there are less restrictive and voluntary alternatives to seclusion such as “soft rooms” which are already known from “Soteria” concepts [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Die genannten Aspekte möglicher Stigmatisierung sind jedoch auch bei der Verlegung von "offenen" auf "geschlossene" Stationen traditionellen Zuschnitts immanent. Zuletzt sei noch angemerkt, dass obwohl offene Türen und flexible Ausgangsregelungen die Anwendung von Zwangsmaßnahmen deutlich reduzieren [24], das Risiko für ein zwischenzeitliches Entweichen von Patienten mit einer Unterbringung nach den Gesetzen zur Unterbringung psychisch Kranker der Bundesländer oder dem BGB ansteigen kann, obwohl empirische Untersuchungen diese naheliegende Vermutung allenfalls in geringen Ausmaß bestätigen [20,24]. Diese Neuorientierung kann bei Amtsrichtern, Polizeibeamten und Menschen in der Nachbarschaft einer psychiatrischen Klinik auf Unverständnis stoßen.…”
Section: Aspekte Der Fort-und Weiterbildung Im Track-konzeptunclassified